Computational Study of The Effect of Structure on Antioxidant Activity and Drug Score of Coumarin Derivatives - Bakti, Andi Budi; Martoprawiro, Muhamad Abdulkadir (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2024)
The presence of reactive oxygen species in the body must be maintained at low concentrations, as an excess can lead to oxidative stress. Coumarin, a secondary metabolite found in plants, exhibits potential as an antioxidant agent. However, the development of synthetic antioxidants based on coumarin remains limited. Computational studies enable the manipulation of coumarin structures to predict antioxidant activity. Correspondingly, this research aimed to investigate the effect of the type, number, and position of substituents on the antioxidant activity and drug score of coumarin derivatives utilizing computational methods, specifically ORCA and OSIRIS Property Explorer software. The results revealed that electron-donating substituents (e.g., OCH₃) could enhance antioxidant activity, while electron-withdrawing substituents (e.g., CHO) tended to reduce it. Substitution on the benzene ring of coumarin exerted a more significant effect on antioxidant activity compared to substitution on the pyrone ring. Compounds such as Umbelliferone, Scoparone, and 3-Bromoscoparone exhibited potential as new antioxidants due to their structural similarity to ascorbic acid or TBHQ. However, further studies are necessary to confirm their development as safe and effective antioxidants free from side effects.